A GEOMETRIC TEST FOR POSSIBLE ANDERSONIAN STRESS USING STRIATED FAULTS - Fry N. (My University, 2003)
A graphical compilation of the rake guides of fault striations of known sense facilitates a simple test for their compatibility with Andersonian stress conditions. A compilation of negative double strike angles, on tracing paper, is superimposed on the rake guide plot. If the two register, the candidate generating stress is given by the relative position and orientation of the two plots.
Keywords: SHEAR STRESS; TECTONIC REGIME; STRESS REGIME; FAULT SLIP